ASHRAE GUIDE FOR HVAC IN HAZARDOUS SPACES - Baucom, Michael K. (ASHRAE, 2021)
ASHRAE Guide for HVAC in Hazardous Spaces 2021 is also dedicated to the individuals who work at oil refineries and chemical manufacturing facilities and put their lives on the line every day to provide us all with the products and services we depend upon daily, in the hope that it can provide meaningful information and make their facilities safer places to work. The guide presents various techniques and methods, as developed and refined over the current and past centuries by countless experts within specific fields of interest. It is written in a manner to ensure that the reader gains intuitive insight into the best possible means to ensure that a space is effectively ventilated and conditioned for various levels of occupancy while preserving all aspects of the safety and health of the occupants and protection of the surrounding facilities.